2017
DOI: 10.3390/ma10080944
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Structural Color Pixels: A Review

Abstract: Inspired by natural photonic structures (Morpho butterfly, for instance), researchers have demonstrated varying artificial color display devices using different designs. Photonic-crystal/plasmonic color filters have drawn increasing attention most recently. In this review article, we show the developing trend of artificial structural color pixels from photonic crystals to plasmonic nanostructures. Such devices normally utilize the distinctive optical features of photonic/plasmon resonance, resulting in high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 109 publications
(123 reference statements)
0
44
0
Order By: Relevance
“…In recent work, we theoretically demonstrated that noble metals can offer strong absorption in ultraviolet and visible (Vis) parts of the EM spectrum, while lossy metals can extend the upper-absorption edge up to the near-infrared (NIR) region [1]. Experimentally, these findings have been demonstrated in many recent research studies [17]- [44]. In one pioneering study, Mattiucci et al showed that impedance matched with thin metamaterials make metals absorbent [26].…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 86%
“…In recent work, we theoretically demonstrated that noble metals can offer strong absorption in ultraviolet and visible (Vis) parts of the EM spectrum, while lossy metals can extend the upper-absorption edge up to the near-infrared (NIR) region [1]. Experimentally, these findings have been demonstrated in many recent research studies [17]- [44]. In one pioneering study, Mattiucci et al showed that impedance matched with thin metamaterials make metals absorbent [26].…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 86%
“…In addition, a huge demand for advanced display technology is placed with the rapid development of mobile and electronic devices and becoming increasingly important in our daily life. Owing to the low power consumption as well as full‐color emission, structural color materials are highly hopeful for constructing optical display devices . In particular, the production of a tunable pattern with well‐arranged primary colors of red, green, and blue (RGB) units is anticipated, which can be achieved via colloidal assembly along with other techniques like micromolding, printing, or lithography.…”
Section: Applicationsmentioning
confidence: 99%
“…With the rapid development of modern detection industries, traditional single stealth approaches, such as visible-light camouflage [ 1 , 2 ] and infrared emissivity engineering [ 3 , 4 , 5 , 6 ], are severely threatened by dual- and multi-approach target detectors [ 7 , 8 ], which were proposed and practically applied in recent years. Hence, the impending compatible camouflage demand of visible light and infrared has aroused extensive research interests, such as developing colored photonic crystals [ 9 ] and chemical pigments [ 10 , 11 ]. Nevertheless, complicated technology and non-controllable colors are still direct obstacles for the large-scale application of camouflage combined with various structure colors and ultra-low emissivity ( ε ).…”
Section: Introductionmentioning
confidence: 99%